Direct comparison of the aging and memory effects of magnetic nanoclusters and nanoparticles - Sankar, C. Raj; Vijayanand, S.; Verma, Seema; Joy, Pattayil Alias (Solid State Communications, 2007)
The magnetic characteristics of a dense magnetic nanoparticle system and a spin glass system consisting of magnetic nanoclusters are compared. Zero field cooled and field cooled magnetization measurements, including aging and memory experiments, of the nanoparticle and the magnetic cluster systems show similar characteristics, suggesting a common origin for the spin glass-type behavior of the magnetic nanoparticle and nanocluster systems. (C) 2006 Published by Elsevier Ltd.
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Low temperature synthesis of nanocrystalline lithium ferrite by a modified citrate gel precursor method - Verma, Seema; Joy, Pattayil Alias (Materials Research Bulletin, 2008)
Single phase nanocrystalline lithium ferrite is synthesized by a modified citrate gel precursor technique. Ferrite nanoparticles of average size of 8 nm, obtained after calcination of the citrate gel Made by the usual method at 450 degrees C, show superparamagnetic behavior. However, small amounts of alpha-Fe(2)O(3) is formed as an impurity phase clue to the initial formation of some gamma-Fe(2)O(3) phase. Oil the other hand, when the pH of the mixed Solution is increased to 7 after the addition of ammonia Solution, a lower calcination temperature of 200 degrees C is sufficient for the formation of single phase lithium ferrite nanoparticles of size 30 nm. No impurity phases are detected when the nanocrystalline powders arc calcined at higher temperatures. The magnetic properties of the ferrite nanoparticles of different sizes obtained by calcining the powders at different temperatures are studied. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Nanostructures; Oxides